Pilot reclamation of a tin mining area using biochar on Bangka Island, Indonesia - Möller, A.; Schütte, P.; Saragi, A.; Ichsan, N.; Franken, G. (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
Indonesia is the world’s second-largest producer of tin. Many tin deposits have formed by sedimentation in the floodplains of rivers. These deposits are mined by physical gravity separation of the heavier tin minerals from the rest of the sediments. What is left is infertile soil with washed-out reactive fine soil fraction and nutrients. They can barely retain water and nutrients, and the pH value of these soils is often very low. Decades of mining on the islands of Bangka and Belitung have left behind large areas of highly degraded soils. Reclamation of these tin mining areas is a complex issue involving technical, socio-economic and legal aspects. Some of these aspects were addressed in a pilot project implemented by the Federal Institute for Geosciences and Natural Resources (BGR) and Indonesian partners on Bangka Island from 2016 to 2019. Biochar, a stable form of carbon that can persist in the soil for thousands of years, can make a valuable contribution to the reclamation of these former tin mining areas by restoring the degraded soil. It can store water and nutrients and contains ash, which raises the pH value of the soil. However, biochar alone is not enough to make infertile soils fertile again. Therefore, in BGR’s pilot project on the island of Bangka, we added other nutrient-rich materials which included a mixture of rice husks and chicken manure complementing biochar in the soils. We have shown that these disturbed areas can be used for agriculture and forestry, such as vegetable cultivation, oil palm plantations and fast-growing trees. In addition, with the use of biochar, carbon can be stored in soil in the long term. Furthermore, the fast revegetation led to a rise of above-ground biomass and consequently to a higher organic carbon content in the topsoil. Thus, mine reclamation can contribute to climate change mitigation. The use of biochar systems can therefore contribute significantly to improving the mine reclamation processes of tin placer deposits.